Bioprospecting of Microalgae Isolated from the Adriatic Sea: Characterization of Biomass, Pigment, Lipid and Fatty Acid Composition, and Antioxidant and Antimicrobial Activity - Marina Grubišić; Božidar Šantek; Zoran Zorić; Zrinka Čošić; Ivna Vrana; Blaženka Gašparović; Rozelindra Čož-Rakovac; Mirela Ivančić Šantek (Molecules, 2022)
Marine microalgae and cyanobacteria are sources of diverse bioactive compounds with potential biotechnological applications in food, feed, nutraceutical, pharmaceutical, cosmetic and biofuel industries. In this study, five microalgae, Nitzschia sp. S5, Nanofrustulum shiloi D1, Picochlorum sp. D3, Tetraselmis sp. Z3 and Tetraselmis sp. C6, and the cyanobacterium Euhalothece sp. C1 were isolated from the Adriatic Sea and characterized regarding their growth kinetics, biomass composition and specific products content (fatty acids, pigments, antioxidants, neutral and polar lipids). The strain Picochlorum sp. D3, showing the highest specific growth rate (0.009 h−1), had biomass productivity of 33.98 ± 0.02 mg L−1 day−1. Proteins were the most abundant macromolecule in the biomass (32.83–57.94%, g g−1). Nanofrustulum shiloi D1 contained significant amounts of neutral lipids (68.36%), while the biomass of Picochlorum sp. D3, Tetraselmis sp. Z3, Tetraselmis sp. C6 and Euhalothece sp. C1 was rich in glycolipids and phospholipids (75%). The lipids of all studied microalgae predominantly contained unsaturated fatty acids. Carotenoids were the most abundant pigments with the highest content of lutein and neoxanthin in representatives of Chlorophyta and fucoxanthin in strains belonging to the Bacillariophyta. All microalgal extracts showed antioxidant activity and antimicrobial activity against Gram-negative E. coli and S. typhimurium and Gram-positive S. aureus.